Exit the colonel : the hidden history of the Libyan revolution - Chorin, Ethan Daniel (New York : PublicAffairs, 2012)
Draws upon interviews with senior American and Libyan officials as well as rebels and loyalists to offer a glimpse into the unraveling of the Qaddafi regime over several decades.
Libya's lot -- Threats and adaptations -- The price is right -- The Americans return -- The great makeover -- Unfinished business -- Cracks apparent -- On the eve of revolution -- Benghazi: the first five days -- The debate over intervention -- Stalemate looms -- The end and a beginning -- Assessment -- Towards the precipice -- The weight of the past.
Includes bibliographical references (pages 347-354) and index.
Keywords: Qaddafi, Muammar; Qaddafi, Muammar; d; Qaddafi, Muammar; 2001; Revolution; 2; Libya -- History -- Civil War, 2011-; Libya; Libyen; Libya -- History -- Civil War, 2011-; History